Prostate Cancer Screening, Yes or No? the Current Controversy - Razi, Ali (Urology Journal, 2009)
Purpose: The increasing incidence of prostate cancer and different viewpoints of medical authorities to it, has lead to conversion of preliminary plan of screening test to a requisite. The objective of this study is to clarify the obscure aspects of this subject using the literature review. Materials and Methods: We reviewed the following items in the literature: prostate cancer screening, introduction of relevant tests, screening criteria according to World Health Organization, screening experience in different countries, community notification, specialists training in order to establish an integrated approach and treatment, anxiety relief, and promotion of patient awareness in this field. Results: It has been shown that, except in China, programmed and official screening of prostatic cancer has not been accepted by concordant responsible authorities, neither in developed countries nor in developing ones. However, it is performed informally in different parts of the world. Conclusion: There is no unanimous consensus about performance of screening for prostate cancer. Continuing voluntary referral of men above 50 years old for performing prostatic specific antigen (PSA) test has been accepted universally and is being done potentially, defined as â€œopportunistic screeningâ€.